PENGARUH EFISIENSI BANK DAN KREDIT BERMASALAH TERHADAP PROFITABILITAS PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK PERIODE 2012-2022 - Santi Nursyahidah; Dede Hendra (Journal of Research and Publication Innovation, 2025)
This study aims to analyze partially and simultaneously the effect of Bank Efficiency and Non-Performing Loans on Profitability at PT Bank Rakyat Indonesia (Persero) Tbk for the period 2012-2022. This research method uses quantitative methods. The population used in this study is sourced from the financial data of the official website of PT Bank Rakyat Indonsia (Persero) Tbk. The sample of this study is financial statement data in the form of balance sheets and profit and loss at PT Bank Rakyat Indonesia (Persero) Tbk for the period 2012 to 2022. The data analysis used includes classical assumption test, simple linear regression test, multiple linear regression test, determination coefficient test, partial test and simultaneous test. The results of this study based on the classical assumption test did not find variables that deviated from the classical assumptions. These results indicate that the available data have met the requirements for using multiple regression equation models. The t test results show that partially Bank Efficiency has no effect on Profitability, this is evidenced by the tcount result greater than the t table 2.158 < t table 2.26216 and the significance level is 0.063> 0.05. Non-performing loans affect profitability, this is evidenced by the results of the tcount smaller than the t table 5.662> t table 2.26216 and the significance level is 0.000 <0.05. And simultaneously Credit Efficiency and Non-Performing Loans affect Profitability, this is evidenced by the results of Fcount greater than Ftable 18.929> 4.26 and the significance level is 0.001 <0.005, with a contribution of 78.2%, while the remaining 21.8% is influenced by other factors.